Preparation method, product and application of oil response type latex

By adding oil response gels in the cement, the problem of decline in the integrity of the existing self -healing material caused by the existing self -healing material, and realized the high toughness, crack resistance and crack self -healing ability of the cement material, which significantly improved the solid The sealing integrity of the well cement ring.

CN119371585APending Publication Date: 2025-01-28TIANJIN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411498589.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

While improving the mechanical properties of cement stone, existing self-healing materials lead to a decrease in the integrity of cement ring sealing and lack effective crack sealing capabilities.

Method used

The development of an oily adhesive lactation. By adding the glue to the cement, it uses its self -healing, fast, and intelligent oil response characteristics to improve the toughness and cracking ability of the cement, and to achieve the self -healing of cracks.

Benefits of technology

The oil response glue can significantly improve the toughness and cracking resistance of cement materials, enhance its sealing integrity, and achieve effective crack blocking and self -healing in the high temperature and high pressure environment of the oil and gas well.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371585A_ABST
    Figure CN119371585A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of drilling and cementing of oilfield development, in particular to a preparation method, a product and application of oil response type latex. The preparation method of the oil response type latex comprises the following steps: step 1, adding an anionic emulsifier and a nonionic emulsifier into water, and dissolving to obtain an emulsifier solution; step 2, mixing an acrylate monomer, styrene, a cross-linking agent and an initiator to form a monomer solution; 3, adding the monomer solution into the emulsifier solution, mixing, and uniformly dispersing to obtain an emulsion; and step 4, reacting the emulsion to obtain the oil response type latex. The oil response type latex can quickly cause swelling when a cement sheath is broken to generate oil channeling, and cracks can be filled by volume expansion of a polymer film, so that the cracks are healed. The product can adapt to high-temperature, high-pressure and oil-gas channeling environments of oil and gas wells, and effective self-healing of cracks is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of drilling and cementing in oil field development, and in particular to a preparation method, product and application of an oil-responsive latex. Background Art

[0002] Cementing is a key process in oil and gas exploration, and its purpose is to establish an oil and gas recovery channel with good sealing performance. The cement ring formed in the cementing project can support the wellbore wall and casing, prevent casing corrosion, control abnormal pore pressure, and isolate inter-formation fluids. The sealing integrity of the cement ring is crucial to the safe operation of oil and gas wells throughout their life cycle. Due to the inherent brittleness of oil well cement, it is easy to be damaged. Microcracks in the matrix and cementing interface are inevitable, resulting in reduced mechanical properties and sealing ability of the cement jacket, and even generating ring pressure and formation fluid channels, which poses a huge hidden danger to the sealing integrity of the wellbore.

[0003] Improving the integrity of cement sheath mainly focuses on improving the toughness and deformation capacity of cement paste and effectively repairing existing microcracks. The toughening method of cement sheath is mainly based on the addition of toughening agents. Typical toughening materials include latex, fiber, whisker and elastic toughness particles. The above materials can only enhance the toughness and crack resistance of cement materials to a certain extent, but the self-healing ability of these materials has not been reported. Autonomous healing is a healing technology with artificial intervention. When cracks occur in cement during service, self-healing agents will be released and solidify the cracks. They mainly include microcapsules, shape memory alloys, mineral admixtures and microorganisms. However, existing self-healing materials will cause the mechanical properties of cement paste to deteriorate. Therefore, it is necessary to develop a self-healing agent that can improve the toughness of cement paste to improve the sealing integrity of cement sheath. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method, product and application of an oil-responsive latex to solve the technical problem that the mechanical properties of cement paste are reduced due to self-healing materials in the prior art. The oil-responsive latex of the present invention has the characteristics of self-healing, rapid and intelligent oil response, and can improve the toughness and crack resistance of cement paste.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is a method for preparing an oil-responsive latex, comprising the following steps:

[0007] Step 1, adding anionic emulsifier and nonionic emulsifier into water and dissolving them to obtain an emulsifier solution;

[0008] Step 2, mixing acrylic ester monomers, styrene, a crosslinking agent and an initiator to form a monomer solution;

[0009] Step 3, adding the monomer solution into the emulsifier solution, mixing and uniformly dispersing into an emulsion;

[0010] Step 4, the emulsion is reacted to obtain an oil-responsive latex.

[0011] In a preferred embodiment of the present invention, in step 1, the anionic emulsifier is sodium lauryl sulfate; and the nonionic emulsifier is alkylphenol polyoxyethylene ether-10.

[0012] In a preferred embodiment of the present invention, in step 1, the mass ratio of the anionic emulsifier, the nonionic emulsifier and water is (1.2-3.5): (1.2-3.5): (80-200). In step 1, the anionic emulsifier and the nonionic emulsifier are fully dissolved in water by stirring for 20-30 minutes.

[0013] In the present invention, the amount of emulsifier is within the range of 1.2-3.5, and the synthesized emulsion is stable and has a low bubble content. If the amount of emulsifier is too small, the emulsifier molecules are not enough to cover the entire oil-water interface, and are arranged loosely on the interface, resulting in the interfacial tension not being able to reach the minimum, and the emulsion system is unstable. If the amount of emulsifier is too large, although the interfacial tension is reduced to the minimum and a stable emulsion is obtained, the foam will increase, affecting the quality of the emulsion, causing inconvenience in use, and also increasing production costs.

[0014] In a preferred embodiment of the present invention, in step 2, the acrylic ester monomer is a mixture of butyl methacrylate and octadecyl methacrylate; the crosslinking agent is divinylbenzene or tripropylene glycol diacrylate; and the initiator is azobisisobutyronitrile or benzoyl peroxide.

[0015] In a preferred embodiment of the present invention, in step 2, the mass ratio of butyl methacrylate, octadecyl methacrylate, styrene, crosslinking agent and initiator is (4-8.3): (6.8-16.2): ​​(12-26.6): (0.16-0.36): (0.4-8).

[0016] In the present invention, the ester chain segments mainly play an affinity role with organic solvent molecules in the three-dimensional polymer network, but the ester monomer is a soft chain segment, and too high a content will result in too low system strength and failure to form a grid that effectively absorbs organic solvents. The polystyrene chain segment is a hard segment, which mainly plays a supporting role in the three-dimensional resin network, but if the styrene content is too high, the rigidity of the polymer molecular chain segment is strong, the chain segment is difficult to stretch, and the affinity with the organic solvent molecules is reduced, resulting in a decrease in oil absorption rate.

[0017] In step 3, an ultrasonic cell crusher is used for uniform dispersion, and the dispersion time is 20-40 minutes.

[0018] In a preferred embodiment of the present invention, in step 4, the reaction temperature is 65-75°C.

[0019] In the present invention, the reaction temperature is limited to 65-75°C for the following reasons: at this reaction temperature, the decomposition efficiency of the AIBN initiator is at a medium level, the degree of polymerization of the polymer is at a medium level, and it has good physical and chemical properties. When the polymerization temperature is too low, there are few active centers generated by the decomposition of AIBN, some unpolymerized monomers exist, the internal structure is unstable, and it is easy to collapse during the oil absorption process, resulting in poor oil absorption effect. When the temperature is too high, the decomposition efficiency of the initiator is too high, which is easy to cause dead-end polymerization, and the possibility of collision and aggregation between latex particles increases, and the stability will decrease.

[0020] In a preferred embodiment of the present invention, in step 4, the reaction time is 4.5-6 hours. The reaction time will affect the degree of polymerization and conversion rate of the polymer. If the reaction time is too short, the polymerization reaction is incomplete and there is a phenomenon of unpolymerized monomers; if the reaction time is too long, energy will be wasted. Therefore, the present invention limits the reaction time to the above parameter range.

[0021] The second technical solution of the present invention is an oil-responsive latex prepared by the above-mentioned preparation method.

[0022] The third technical solution of the present invention is the application of the above oil-responsive latex in cementing engineering, specifically in the toughening of oil well cement and crack plugging.

[0023] The fourth technical solution of the present invention is a method for improving the toughness and crack resistance of cement materials, which improves the toughness and crack resistance of cement materials by adding the above-mentioned oil-responsive latex to cement. The addition amount of the oil-responsive latex is 5%-8% of the mass of the cement.

[0024] The present invention discloses the following technical effects:

[0025] 1. The preparation process of the present invention is simple and easy to operate, the raw materials are widely available, and it is easy to apply in large-scale engineering.

[0026] 2. The colloidal particles in the oil-responsive latex of the present invention are adsorbed and accumulated between the hydration products and the pores to form a flexible and uniform film, which refines the pore structure and thus forms a more uniform and dense microstructure. The polymer film can absorb stress and bridge microcracks, thereby improving the toughness and crack resistance of cement materials.

[0027] 3. When the cement sheath breaks and oil channeling occurs, the oil-responsive latex of the present invention can rapidly cause swelling, and the volume expansion of the polymer film can fill the cracks, thereby causing the cracks to heal. The product can adapt to the high temperature and high pressure and oil and gas channeling environment of oil and gas wells, and achieve effective self-healing of cracks.

[0028] 4. The oil-responsive latex of the present invention can enhance the toughness and crack resistance of cement materials and endow them with crack self-healing ability, thereby improving the sealing integrity of cement ring from the two aspects of "combining prevention and treatment". BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 This is the infrared spectrum of the oil-responsive latex prepared in Example 3.

[0031] Figure 2 (a) is a graph showing the flexural strength of pure cement and the oil-responsive latex-modified cement paste prepared in Example 3; (b) is a graph showing the stress-strain curves of pure cement and the oil-responsive self-healing toughening latex-modified cement paste prepared in Example 3.

[0032] Figure 3 The microstructure diagram of pure cement and the oil-responsive self-healing toughening emulsion modified cement paste prepared in Example 3.

[0033] Figure 4 (a) is a statistical diagram of the width of artificial cracks in cement stone; (b) is a characterization diagram of the self-healing ability of pure cement and cement stone modified with the oil-responsive self-healing toughening emulsion prepared in Example 3. DETAILED DESCRIPTION

[0034] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0035] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0039] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0040] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0041] Example 1

[0042] A method for preparing an oil-responsive latex, comprising the following steps:

[0043] Step 1, dissolve 2g of sodium dodecyl sulfate and 2g of alkylphenol polyoxyethylene ether-10 in 160g of deionized water in order by mass to obtain an emulsifier solution.

[0044] Step 2: 32 g of octadecyl methacrylate, 48 g of styrene, 0.32 g of divinylbenzene and 0.8 g of benzoyl peroxide are mixed in order by mass to form a monomer solution.

[0045] Step 3: Mix the monomer solution prepared in step 2 with the emulsifier solution prepared in step 1, and evenly disperse them using an ultrasonic cell crusher under ice-water bath conditions to prepare a stable pre-emulsified emulsion.

[0046] Step 4: The pre-emulsified emulsion prepared in step 3 is reacted at 70° C. for 5 hours to obtain an oil-responsive self-healing toughening emulsion (ie, oil-responsive latex).

[0047] Example 2

[0048] A method for preparing an oil-responsive latex, comprising the following steps:

[0049] Step 1, dissolve 2g of sodium dodecyl sulfate and 2g of alkylphenol polyoxyethylene ether-10 in 160g of deionized water in order by mass to obtain an emulsifier solution.

[0050] Step 2: 32 g of butyl methacrylate, 48 g of styrene, 0.32 g of divinylbenzene and 0.8 g of benzoyl peroxide are mixed in order by mass to form a monomer solution.

[0051] Step 3: Mix the monomer solution prepared in step 2 with the emulsifier solution prepared in step 1, and evenly disperse them using an ultrasonic cell crusher under ice-water bath conditions to prepare a stable pre-emulsified emulsion.

[0052] Step 4: The pre-emulsified emulsion prepared in step 3 is reacted at 70° C. for 5 hours to obtain an oil-responsive self-healing toughening emulsion (ie, oil-responsive latex).

[0053] Example 3

[0054] A method for preparing an oil-responsive latex, comprising the following steps:

[0055] Step 1, dissolve 2g of sodium dodecyl sulfate and 2g of alkylphenol polyoxyethylene ether-10 in 160g of deionized water in order by mass to obtain an emulsifier solution.

[0056] Step 2: 13 g of butyl methacrylate, 26 g of octadecyl methacrylate, 39 g of styrene, 0.32 g of divinylbenzene and 0.8 g of benzoyl peroxide are mixed in order by mass to form a monomer solution.

[0057] Step 3: Mix the monomer solution prepared in step 2 with the emulsifier solution prepared in step 1, and evenly disperse them using an ultrasonic cell crusher under ice-water bath conditions to prepare a stable pre-emulsified emulsion.

[0058] Step 4: The pre-emulsified emulsion prepared in step 3 is reacted at 70° C. for 5 hours to obtain an oil-responsive self-healing toughening emulsion (ie, oil-responsive latex).

[0059] Example 4

[0060] A method for preparing an oil-responsive latex, comprising the following steps:

[0061] Step 1, dissolve 2g of sodium dodecyl sulfate and 2g of alkylphenol polyoxyethylene ether-10 in 160g of deionized water in order by mass to obtain an emulsifier solution.

[0062] Step 2: 13 g of butyl methacrylate, 26 g of octadecyl methacrylate, 39 g of styrene, 0.32 g of tripropylene glycol diacrylate and 0.8 g of benzoyl peroxide are mixed in order by mass to form a monomer solution.

[0063] Step 3: Mix the monomer solution prepared in step 2 with the emulsifier solution prepared in step 1, and evenly disperse them using an ultrasonic cell crusher under ice-water bath conditions to prepare a stable pre-emulsified emulsion.

[0064] Step 4: The pre-emulsified emulsion prepared in step 3 is reacted at 70° C. for 5 hours to obtain an oil-responsive self-healing toughening emulsion (ie, oil-responsive latex).

[0065] Example 5

[0066] A method for preparing an oil-responsive latex, comprising the following steps:

[0067] Step 1, dissolve 2g of sodium dodecyl sulfate and 2g of alkylphenol polyoxyethylene ether-10 in 160g of deionized water in order by mass to obtain an emulsifier solution.

[0068] Step 2: 13 g of butyl methacrylate, 26 g of octadecyl methacrylate, 39 g of styrene, 0.32 g of divinylbenzene and 0.8 g of azobisisobutyronitrile are mixed in order by mass to form a monomer solution.

[0069] Step 3: Mix the monomer solution prepared in step 2 with the emulsifier solution prepared in step 1, and evenly disperse them using an ultrasonic cell crusher under ice-water bath conditions to prepare a stable pre-emulsified emulsion.

[0070] Step 4: The pre-emulsified emulsion prepared in step 3 is reacted at 70° C. for 5 hours to obtain an oil-responsive self-healing toughening emulsion (ie, oil-responsive latex).

[0071] In order to verify the effect of the oil-responsive monomer on the oil absorption capacity of the oil-responsive latex, the oil absorption capacity of the oil-responsive latex prepared in Example 1, Example 2, Example 3, Example 4 and Example 5 was tested. The results are shown in Table 1.

[0072] Table 1 Oil absorption capacity of oil-responsive latex

[0073]

[0074] As can be seen from Table 1, compared with Example 2 in which only butyl methacrylate is introduced, Example 1 in which only octadecyl methacrylate monomer is introduced has a stronger oil absorption capacity, resulting in a larger oil absorption expansion volume. The reason is that the alkyl chain of the copolymer in which only butyl methacrylate is introduced is shorter, so it is difficult to crosslink into a three-dimensional network structure, which reduces the effective oil absorption and oil storage volume. At the same time, the small number of ester groups as lipophilic groups will also affect the oil absorption effect. At the same time, long-chain octadecyl methacrylate has a stronger affinity for oil products and can give the emulsion a stronger oil absorption performance. However, long alkyl chains are easily entangled together, making the resin structure relatively soft and unable to form a stable structure, which will affect the oil absorption capacity of the polymer; therefore, part of the methyl methacrylate monomer is introduced into Example 1, and an appropriate amount of short-chain monomers make the polymerized polymer have a long and short staggered structure. This three-dimensional structure is very conducive to oil absorption and increases the oil absorption amount. Comparing Example 3 and Example 4, in terms of oil absorption capacity, the crosslinking agent divinylbenzene is better than tripropylene glycol diacrylate. Figure 1 The molecular structure formula of the oil-responsive self-repairing toughening emulsion generated by emulsion polymerization in Example 3 is listed in FIG. -1 、3059cm -1 and 3086cm -1 The peak at 759 cm corresponds to the stretching vibration of C=H on the benzene ring, while the peak at 759 cm -1 and 698cm -1 The strong peak at 1725 cm is the main absorption peak of the monosubstituted benzene ring (the out-of-plane bending vibration of the CH bond in the C=CH on the carbon skeleton of the benzene ring). -1 The stretching vibration peak appears at 2925cm -1 and 2853cm -1 Methyl and methylene stretching vibration peaks were observed at 140°C. It can be seen that the emulsion prepared in this example is a copolymer of butyl methacrylate, octadecyl methacrylate and styrene.

[0075] Figure 2-4 BCHP in the middle represents cement paste without adding oil-responsive self-healing toughening emulsion, PHCP-5 and PHCP-8 represent cement paste added with 5% and 8% oil-responsive self-healing toughening emulsion, respectively.

[0076] Subsequently, in order to evaluate the toughening effect of the oil-responsive self-healing toughening emulsion prepared in the present invention on the cement ring of cementing, the mechanical properties of the tough cement slurry prepared in Example 3 after curing were tested. The preparation method of the cement sample and the test of the mechanical properties were carried out in accordance with GB / T19139-2012 "Test Methods for Oil Well Cement". Figure 2 (a) and Figure 2(b) shows the effect of different contents of the oil-responsive self-healing toughening emulsion prepared in Example 3 on the flexural strength and stress-strain of cement paste.

[0077] from Figure 2 It can be seen in (a) that the flexural strength of the cement sample increases with the increase of emulsion content. The flexural strength of cement paste containing 5% and 8% emulsion increased by 13.3% and 14.1% respectively compared with the strength of pure cement after 3 days of curing. As the curing time is extended to 28 days, the flexural strength of cement paste with an oil-responsive self-healing toughening emulsion addition of 5% of the cement mass increased by 25.9% compared with the strength of pure cement, and the flexural strength of cement paste with 8% emulsion addition increased by 29.9% compared with pure cement. In order to further illustrate the toughening effect of oil-responsive self-healing toughening emulsion on cement paste, a uniaxial test was carried out on it. The elastic modulus can be calculated from the uniaxial curve, which can more intuitively represent the toughening properties of the emulsion on cement paste. From Figure 2 It can be seen in (b) that when the stress is small, the stress-strain of the blank cement paste and the oil-responsive self-healing toughening emulsion-modified cement paste is positively correlated. When the stress is large, the blank cement paste exhibits plastic deformation, while the emulsion-modified cement paste exhibits elastic deformation. Table 2 shows the elastic modulus of pure cement paste and oil-responsive self-healing toughening emulsion-modified cement paste. As shown in Table 2, the elastic modulus of the blank cement paste is 11.1 GPa, the elastic modulus of the cement paste with 5% emulsion content is 6.27 GPa, and the elastic modulus of the cement paste with 8% emulsion content is 5.69 GPa. Compared with pure cement paste, the elastic modulus of the cement paste with 5% emulsion content and the elastic modulus of the cement paste with 8% emulsion content are reduced by 43.5% and 48.7%, respectively. These results show that the emulsion-modified cement paste has better toughness before failure.

[0078] Table 2 Elastic modulus of pure cement paste and cement paste modified by oil-responsive self-healing toughening emulsion

[0079]

[0080] During cement hydration and water evaporation, colloidal particles undergo four processes: concentration, dense accumulation, deformation, and film formation. Finally, the colloidal particles form a thin film on the surface of the cement hydration product. In order to further explore the toughening mechanism of the oil-responsive self-healing toughening emulsion prepared by the present invention, the emulsion-modified cement stone prepared in Example 3 was subjected to SEM analysis. Figure 3 (a) shows that the blank cement sample contains a large number of harmful pores and microcracks, resulting in poor pore structure, high porosity and low toughness. Figure 3It can be seen in (b) that after adding 5% oil-responsive self-healing toughening emulsion, the pores of cement paste are reduced and the microstructure is more uniform and dense. This is because the colloidal particles are adsorbed and accumulated between the hydration products and the pores, forming a flexible and uniform film. A two-phase space network structure that permeates with cement is formed, making the microstructure more uniform and dense. Figure 3 (c) shows that with the increase of emulsion dosage (8%), the pore defects of cement are further reduced, and the structure is denser and smoother. The formation of polymer film and the reduction of pore structure improve the toughness and crack resistance of cement materials.

[0081] The self-healing test was carried out on pure cement stone and cement samples containing the oil-responsive self-healing toughening emulsion prepared in Example 3 using a self-healing cement evaluation test instrument (SHCE-2019). The test used sealing pressure and emulsion addition as variables. The test method is based on the national standard GB / T19139-2012. Its working principle is to pressurize the cement column with nitrogen so that the oil above the cement column invades the cement column. If the cement sample has self-healing properties, the liquid will not flow out from the lower outlet. As the nitrogen pressure increases, when the discharge hole begins to discharge liquid, the pressure at this time is the critical maximum pressure of the plugging, also known as the breakthrough pressure. A cylindrical cement sample with a diameter of 5 cm and a height of 2.5 cm was prepared. Through the Brazilian splitting experiment, through cracks similar to the geometry of naturally occurring cracks were generated on the sample. A two-liquid mixed hardening adhesive (acrylic glue) was used to firmly stick the peripheral cracks of the sample and seal all edge gaps to prevent possible liquid leakage. The cracks of the cement sample used for the Brazilian splitting test were uneven and the crack surface was not flat. Figure 4 (a) shows the distribution statistics of crack width, and the crack width of all samples is similar. Oil flow test was carried out on the cement samples to verify the self-healing ability of cracked cement, such as Figure 4 As shown in (b). The blank cement sample reached a breakthrough pressure of 0.006MPa within a few minutes. Due to the lack of self-healing ability, the breakthrough pressure did not change with time. The sealing pressure of the cement stone sample modified by the oil-responsive self-healing toughening latex increased with time. The cement stone with 5% and 8% emulsion additions reached the limit values ​​of 0.076MPa and 0.122MPa at 120min and 160min, respectively. It can be seen that under oil flow conditions, the self-healing emulsion can respond well to oil to achieve crack sealing of damaged cement samples.

[0082] The oil-responsive self-healing toughening emulsion of the present invention has intelligent response behavior, can effectively improve the self-healing ability of the cement matrix, and can significantly improve the toughness and crack resistance of the cement matrix. The oil-responsive self-healing toughening emulsion has a micro-cross-linked three-dimensional network structure, and the introduction of long and short chain alkyl groups enhances the affinity for oil, so that its polymer film can achieve crack healing through oil expansion. At the same time, it is prepared by emulsion polymerization, because the significant film-forming property of the emulsion polymer can give the cement matrix good toughness and crack resistance. The emulsion with both toughness and self-healing ability is of certain significance to the long-term sealing stability of the cement ring of the cementing well.

[0083] The oil-responsive latex prepared by the method of the present invention can improve the annular deformation ability and toughness of cementing cement, effectively improve the brittle defects of the cement sheath, and endow it with crack healing ability, thereby promoting the sealing integrity of the cement sheath.

[0084] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing an oil-responsive latex, characterized in that: The following steps are involved: Step 1, adding anionic emulsifier and nonionic emulsifier into water and dissolving them to obtain an emulsifier solution; Step 2, mixing acrylate monomers, styrene, a crosslinking agent and an initiator to form a monomer solution; Step 3, adding the monomer solution to the emulsifier solution, mixing and uniformly dispersing into an emulsion; Step 4, the emulsion is reacted to obtain an oil-responsive latex.

2. The method for preparing the oil-responsive latex according to claim 1, characterized in that: In step 1, the anionic emulsifier is sodium lauryl sulfate; and the nonionic emulsifier is alkylphenol polyoxyethylene ether-10.

3. The method for preparing the oil-responsive latex according to claim 1, characterized in that: In step 1, the mass ratio of the anionic emulsifier, the nonionic emulsifier and water is (1.2-3.5):(1.2-3.5):(80-200).

4. The method for preparing the oil-responsive latex according to claim 1, characterized in that: In step 2, the acrylic ester monomer is a mixture of butyl methacrylate and octadecyl methacrylate; the crosslinking agent is divinylbenzene or tripropylene glycol diacrylate; and the initiator is azobisisobutyronitrile or benzoyl peroxide.

5. The method for preparing the oil-responsive latex according to claim 4, characterized in that: In step 2, the mass ratio of butyl methacrylate, octadecyl methacrylate, styrene, crosslinking agent and initiator is (4-8.3): (6.8-16.2): ​​(12-26.6): (0.16-0.36): (0.4-8).

6. The method for preparing the oil-responsive latex according to claim 1, characterized in that: In step 4, the reaction temperature is 65-75°C.

7. The method for preparing the oil-responsive latex according to claim 1, characterized in that: In step 4, the reaction time is 4.5-6h.

8. The oil-responsive latex prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the oil-responsive latex as claimed in claim 8 in cementing engineering.

10. A method for improving the toughness and crack resistance of cement materials, characterized in that: By adding the oil-responsive latex described in claim 8 to cement, the toughness and crack resistance of the cement material can be improved.

Citation Information

Patent Citations

  • Polymer latex for cement-base material oil absorption and expansion and preparation method thereof

    CN104177555A

  • Preparation method of self-healing agent for oil well cement, well cementation self-healing cement slurry and application

    CN104418965A

  • Self-Repairing Cements

    US20130146286A1